AB0900 Kawasaki Diseasein Infants: Clinical Data of Kawasaki Patients in Tyrol from 2003-2012. (10th June 2014) - Binder, E.; Brunner, J.; Griesmaier, E.; Giner, T.; Sailer-Hoeck, M.
Abstract : Background: Kawasaki disease (KD) is a rare vasculitis seen predominantly in children. In developing countries, it is the leading cause of childhood-acquired heart disease. Besides a case report from 1981 there have beenno data published dealing with the epidemiology and clinical aspects of KD in Austria. Objectives: The purpose of the present study was to investigate the clinical spectrum of KDin an entire geographically determined cohort of infants that were diagnosed and treated at the University Hospital of Innsbruck from 2003-2012. Methods: 32 patients were included in the study with a median age of 32.96 months (2-192). 59.4% of the patients were aged between six months and four years. The male-to-female ratio was 1:1.13. Results: Clinical examination revealed non-purulent conjunctivitis and exanthema as the most common symptoms (84.4%). 75% showed oropharyngeal changes, 21.9% had gastrointestinal complaints such as diarrhoe, stomach ache or vomiting prior to diagnosis. One third of the patients were admitted with a preliminary diagnosis, whereas 78.1% were pre-treated with antibiotics.The median fever duration at the time of presentation was estimated with 4.96 days (1-14), at time of diagnosis 6.76 days (3-15).75% were diagnosed with complete, 25% with incomplete KD. There was no significant difference in the duration of fever neither between complete and incomplete KD nor between the different age groups.Typical laboratory findings included increased C-reactive protein (CRP) (80.6%) and erythrocyte sedimentation rate (ESR) (96%), leukocytosis (48.4%) and thrombocytosis (40.6%) without any significant quantitative difference between complete and incomplete KD.Coronary complications could be observed in six patients, one with a coronary aneurysm and five with tubular dilatation of the coronary arteries.Our patient cohort represents the age distribution as described in literature and emphasizes that KD could affect persons of any age. The frequency of occurrence of the clinical symptoms differs from previous reports – whilst peripheral desquamation is reported as one of the most common symptom, in our study, we predominantly observed non-purulent conjunctivitis and exanthema. Conclusions: KD should always be considered as a differential diagnosis in a child or adult with fever of unknown origin, as treatment can significantly decrease the frequency of coronary complications. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.4872